Analisis Tingkat Efisiensi dan Efektivitas Pengelolaan Keuangan Daerah di Kabupaten Waropen - Pieter Noisirifan de Fretes (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The aims of this research are; (1) To find out the structure of the financial relationship between the central government and regional governments in terms of revenues from the 2019 budget year to the 2023 budget year, (2) To find out how big the growth rate of routine revenues and expenditures is from the 2019 to 2023 budget year, ( 3). To find out the level of efficiency and effectiveness of regional financial management in Waropen Regency, and (4) To find out how revenues influence Waropen Regency's routine expenditure from the 2019 to 2023 budget year. Analysis tools; (1). Analysis of the Structure of Central and Regional Financial Relations (2). Efficiency Analysis and Effectiveness Analysis, (3). Growth Analysis and (4). Correlation Analysis. Analysis Results: The financial relationship between the central and regional governments shows that the PAD to TPD ratio of the Waropen Regency Government is classified as good, namely 6.96 percent. The growth rate of revenue for the Waropen Regency Government is an average of 17.27 percent, while the growth rate of routine expenditure fluctuates greatly , with an average growth of 32.41 percent. Financial management in the Waropen Regency Government is still relatively efficient and effective. The close relationship between revenue and routine expenditure of the Waropen Regency Government is 96.6 percent.